Role of birthweight discordance in preterm twins' outcomes in the Korean neonatal network - Sook Kyung Yum; Jung Hyun Lee (Elsevier, 2023)
Background: Twin pregnancies can be complicated by birthweight (BW) discordance. We analyzed the impact of BW discordance on clinical outcomes of very-low-birthweight (VLBW) twins. Methods: The study population was preterm infants in the Korean Neonatal Network registry. Multivariate logistic regression analyses were used to determine the contribution of BW discordance on respiratory morbidities and mortality of VLBW infants. Also, we assessed the effect of small for gestational age (SGA) on morbidity and mortality in discordant twins (DTs) and compared separately the clinical outcomes of smaller and larger DTs with different singletons matched for perinatal factors including BW percentile. Results: A total of 935 twin pairs [1548 concordant twins (CTs) and 322 DTs] were included. BW discordance was associated with increased odds of moderate bronchopulmonary dysplasia, mortality, and composite outcomes. Compared with the CTs, the smaller, but not larger, DTs had greater odds of morbidities and mortality. DTs had higher odds of adverse neonatal outcome when combined with SGA. Meanwhile, DTs had morbidities and mortality similar to singletons matched for BW percentile. Conclusion: BW discordance in VLBW twins adversely affects neonatal mortality or respiratory morbidity which is predominant in smaller DTs. The impact of BW discordance could be increased through SGA.